(untitled) (Sociologisk Forskning, 1993)
Politics, issues and voters in the Swedish 1991 election The 1991 elections to the Swedish Riksdag resulted in a major setback for the Social Democrats, which have dominated Swedish politics since the 1930s. The party received a lower share of the votes than it had done since the 1920’s. The background to this defeat is here discussed largely on the bases of secondary analyses of opinion polls. Although longterm structural changes in Swedish society and internationally may have contributed to the defeat, its immediate background would appear to have been the new economic policies which the Social Democratic government initiated since 1982 and which gradually come to alienate the core of the grassroot supporters of the party.